Combined spinal cord stimulation and intrathecal Morphine–Sufentanil therapy for refractory cancer pain: a case report - Zhang, Zhi Shan; Zhang, Yi; Wu, Jie (Frontiers in Aging, 2026)
This case report describes the management of a 61-year-old female patient with metastatic adenoid cystic carcinoma and chronic refractory cancer pain. Initially treated with spinal cord stimulation (SCS), she later developed tolerance and inadequate analgesia. An intrathecal drug delivery system (IDDS) was subsequently implanted, and combination therapy with intrathecal morphine and sufentanil was initiated. This regimen achieved significant pain relief, reduced Numerical Rating Scale (NRS) scores, and improved sleep quality as measured by the Pittsburgh Sleep Quality Index (PSQI). The case highlights the potential efficacy of combining neuromodulation and intrathecal analgesia in managing complex cancer pain. However, due to limited data on sufentanil use in IDDS and the absence of standardized conversion protocols, further studies are warranted.